A non-magnetic hard alloy composite material and preparation method thereof
Through the use of nickel coating layer and lanthanum oxide doped ultrafine composite powder, combined with the application of wear-resistant and anti-corrosion coatings, the problem of poor sintering properties of WC-Ni carbide is solved, and the hardness and resistance of magnetic-free carbide is significantly improved. Abrasiveness achieves higher density and corrosion resistance.
Patent Information
- Application Number
- CN202410878808.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-02
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-07-02
AI Technical Summary
The sintering properties and mechanical properties of WC-Ni carbide are poorer than those of WC-Co carbide, resulting in lower hardness and insufficient wear resistance. The low wetting and low solubility of nickel on the surface of tungsten carbide reduces the sintering properties.
Tungsten carbide is treated by nickel precursor solution to form a nickel coating layer, lanthanum oxide doped ultrafine composite powder is prepared in combination with ball milling and hydrothermal method, and wear-resistant anticorrosion coatings are used to improve the density and corrosion resistance of the alloy.
It significantly improves the hardness, wear resistance and corrosion resistance of magnetic-free carbide. Through the uniform distribution of nickel coating layer and lanthanum oxide doping, the density and structural stability of the alloy are enhanced, and at the same time, the wear-resistant and anti-corrosion coatings are used. The organic-inorganic cross-linking network improves the adhesion and corrosion resistance of the coating.
Smart Images

Figure CN118835118B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cemented carbide, in particular to a non-magnetic cemented carbide composite material and a preparation method thereof. Background Art
[0002] For decades, people have been trying to find alternatives to the cobalt binders commonly used in cobalt-based cemented carbides due to resource depletion, toxicity of cobalt, higher requirements for corrosion resistance, or the need for non-magnetism. Nickel is one of the most promising cobalt substitutes. Since the invention of WC-Ni cemented carbide, people have conducted a lot of research on it. Compared with Co, Ni has lower cost, higher corrosion resistance, non-magnetic behavior and higher fracture toughness, which makes it an attractive binder in corrosive environments and other special applications. For example, Chinese patent application CN101265544A discloses a vanadium-containing non-magnetic cemented carbide and its preparation method. The composition and weight percentage of the alloy are: tungsten carbide: 75% to 90%, nickel powder: 8% to 20%, chromium carbide: 0.5% to 3.0%, vanadium carbide: 0.3% to 2.5%. Its production method includes batching, wet grinding, drying, pressing, sintering, inspection and other processes. The wet grinding process uses a non-magnetic alloy liner wet grinder, adding alcohol or acetone as As grinding medium, non-magnetic carbide balls are used as grinding materials, the ball-to-material ratio is 5:1, the solid-liquid ratio is 350mL / Kg, the wet grinding time is 48 to 56 hours, and the pressure sintering technology is used. Fine-grained tungsten carbide powder (1.0 to 1.5μm) is used as the hard phase to improve the hardness and wear resistance of the alloy. Nickel is used as a binder and a small amount of chromium carbide and vanadium carbide are added as tungsten carbide grain growth inhibitors to refine the tungsten carbide grains and further improve the hardness and wear resistance of the alloy. However, the low wettability of Ni on the WC surface and the low solubility of WC in Ni reduce the sintering and mechanical properties of the sintered carbide, resulting in WC-Ni carbide having worse hardness and insufficient wear resistance compared with WC-Co carbide. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a method for preparing a non-magnetic cemented carbide composite material, comprising the following steps:
[0004] Step (1) treating tungsten carbide with a nickel precursor solution to obtain nickel-coated tungsten carbide;
[0005] Step (2) mixing nickel-coated tungsten carbide, yttrium powder and chromium carbide powder, ball milling, drying, grinding and sieving to obtain a composite powder;
[0006] Step (3) treating the composite powder with lanthanum chloride hexahydrate, and using ball milling combined with surfactant-assisted hydrothermal method to obtain lanthanum oxide-doped ultrafine composite powder;
[0007] Step (4) mixing the lanthanum oxide doped ultrafine composite powder, molybdenum powder and silicon carbide whiskers, ball milling, drying, grinding and sieving to obtain a premix;
[0008] Step (5) forming the premix by dry pressing into a rough blank, then performing cold isostatic pressing to form a green body, and finally performing microwave sintering to obtain a non-magnetic hard alloy;
[0009] Step (6) spraying the wear-resistant and anti-corrosion coating on the surface of the non-magnetic cemented carbide, heat treating, and curing to obtain a non-magnetic cemented carbide composite material;
[0010] The method for preparing the wear-resistant and anti-corrosion coating comprises the following steps:
[0011] Step S1, preparing a modified binder and hydrophobically modified nano-alumina;
[0012] Wherein, preparing the modified binder comprises the following steps:
[0013] Using black phosphorus nanosheets, tannic acid and cerium nitrate as raw materials, reacting to obtain modified black phosphorus nanosheets;
[0014] Aluminum hydroxide reacts with phosphoric acid to obtain an aluminum phosphate binder, which then reacts with modified black phosphorus nanosheets to obtain a modified binder;
[0015] The preparation of hydrophobically modified nano-alumina comprises the following steps:
[0016] The nano-alumina is modified by chitosan and 3-(2,3-epoxypropoxy)propyltrimethoxysilane to obtain surface-modified nano-alumina;
[0017] The surface-modified nano-alumina is treated with oleic acid to obtain hydrophobic-modified nano-alumina;
[0018] Step S2: The hydrophobically modified nano-alumina reacts with the modified binder to obtain a wear-resistant and anti-corrosion coating.
[0019] Preferably, in step (1), the preparation method of nickel-coated tungsten carbide is as follows: adding a nickel precursor solution to tungsten carbide powder, evaporating, and heating to 480-520° C. at a heating rate of 5-10° C. / min in an argon atmosphere to obtain nickel-coated tungsten carbide, wherein the nickel content in the nickel-coated tungsten carbide is 12-16wt%; the nickel precursor solution is obtained by mixing nickel nitrate hexahydrate, nickel acetate tetrahydrate, and triethanolamine in a molar ratio of (8-10):1:(4.5-5.5);
[0020] Preferably, in step (2), the mass ratio of nickel-coated tungsten carbide, yttrium powder and chromium carbide powder is (82.4-83.6):(0.1-1.2):(0.6-0.8); drying conditions: drying at 70-90°C for 2-3h; sieving mesh size is 180-200 mesh; ball milling conditions: ball-to-material ratio is (2-4):1, solid-liquid ratio is 1:(3-6), ball milling speed is 34-36r / min, and ball milling time is 36-64h;
[0021] Preferably, in the step (3), the preparation method of lanthanum oxide doped ultrafine composite powder is as follows: cetyltrimethylammonium bromide and composite powder are added to deionized water, stirred at a speed of 120-160r / min for 20-40min at room temperature, lanthanum chloride hexahydrate is added, stirring is continued for 60-90min, ammonia water is added dropwise at a speed of 0.5-1mL / min, stirred at a speed of 400-500r / min for 20-40min, transferred to a closed container, reacted at 170-180°C for 20-28h, cooled to room temperature, filtered, washed, and dried to obtain lanthanum oxide doped ultrafine composite powder with a particle size of 100-300nm; wherein the mass ratio of cetyltrimethylammonium bromide, composite powder added to deionized water, lanthanum chloride hexahydrate, and ammonia water is (7.3-14.6):(8.9-18):(200-500):(0.03-0.1):(4.5-9).
[0022] Preferably, in step (4), the mass ratio of lanthanum oxide doped ultrafine composite powder, molybdenum powder and silicon carbide whisker is (82-83.5):0.7:(0.9-2); drying conditions: drying at 70-90°C for 2-3h; sieving mesh size is 80-120 mesh; ball milling conditions: ball milling speed is 200-300r / min, ball milling time is 100-150min, ball to material ratio is (6-8):1, and solid-liquid ratio is 1:(3-6).
[0023] Preferably, in step (5), the cold isostatic pressing method is: the pressure is increased to 200-300 MPa within 3-5 minutes, and the pressure is maintained for 3-5 minutes.
[0024] Preferably, in step (5), the microwave sintering method is: in an argon atmosphere, the temperature is increased from room temperature to 900-1000°C at a heating rate of 3-5°C / min and kept at that temperature for 10-20 minutes, then the temperature is increased to 1450-1500°C at a heating rate of 15-20°C / min and kept at that temperature for 10-15 minutes, and then naturally cooled to room temperature.
[0025] Preferably, in step (6), the spray thickness of the wear-resistant and anti-corrosion coating is 100-120 μm; the heat treatment method is: heat treatment at 110-120° C. and 210-220° C. for 50-70 min each.
[0026] Furthermore, in step (6), the method for preparing the wear-resistant and anti-corrosion coating specifically comprises the following steps:
[0027] Step S1, preparing a modified binder and hydrophobically modified nano-alumina;
[0028] Wherein, preparing the modified binder comprises the following steps:
[0029] In a dark environment and nitrogen atmosphere, the black phosphorus nanosheet dispersion was ultrasonically treated for 80-120 min, tannic acid was added, and the reaction was stirred at a speed of 150-250 r / min for 4.5-5.5 h, and then cerium nitrate was added, and the reaction was continued for 3.5-4.5 h, centrifuged, and washed to obtain modified black phosphorus nanosheets, wherein the mass ratio of black phosphorus nanosheets, tannic acid, and cerium nitrate was 1:(1-1.2):(0.15-0.25);
[0030] In the above process, tannic acid self-polymerizes on the surface of black phosphorus nanosheets to form polytannic acid, and polytannic acid directly forms PC covalent bonds with nano black phosphorus sheets. A large number of oxygen-containing groups in polytannic acid complex with cerium to obtain modified black phosphorus nanosheets covalently grafted with polytannic acid and loaded with cerium.
[0031] Aluminum hydroxide and 50-60wt% phosphoric acid aqueous solution are mixed in a mass ratio of 23.4:(16.3-19.6), and stirred at 90-100°C for 150-200min to obtain an aluminum phosphate binder; the aluminum phosphate binder is added to deionized water, ultrasonically treated for 10-20min, and then modified black phosphorus nanosheets are added and stirred for 10-20min to obtain a modified binder; wherein the mass ratio of the aluminum phosphate binder, deionized water, and modified black phosphorus nanosheets is (3.5-8.4):(10-20):(0.3-0.9);
[0032] In the above process, aluminum hydroxide reacts with phosphoric acid to generate aluminum phosphate, and the aluminum phosphate dehydrates and condenses with the hydroxyl groups in the modified black phosphorus sheet to obtain a modified binder.
[0033] The preparation of hydrophobically modified nano-alumina comprises the following steps:
[0034] Disperse chitosan in N,N-dimethylformamide under stirring conditions, add 3-(2,3-epoxypropoxy)propyltrimethoxysilane, stir and react at 75-85°C for 20-28h, then add nano-alumina, keep the temperature unchanged and continue to stir and react for 20-28h, centrifuge, wash, and dry to obtain surface-modified nano-alumina; wherein the mass ratio of chitosan, N,N-dimethylformamide, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and nano-alumina is (2-5):(190-475):(0.5-1):(2.5-3.5);
[0035] In the above process, part of the amino groups in chitosan react with the epoxy groups in 3-(2,3-epoxypropyloxy)propyltrimethoxysilane, and the silicon-oxygen bonds in the resulting reaction product are hydrolyzed into silanols that react with the hydroxyl groups on the surface of the nano-alumina, thereby introducing a chitosan cross-linked network structure containing a large number of hydroxyl groups and amino groups on the surface of the nano-alumina.
[0036] Dissolve oleic acid in N,N-dimethylformamide, then add N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide, stir at a speed of 200-300r / min for 2.5-3.5h, then add surface-modified nano-alumina under stirring, adjust the pH of the reaction mixture to 5.4-5.6 with 1mol / L hydrochloric acid aqueous solution, react in a nitrogen atmosphere for 20-28h, filter, wash and dry after the reaction to obtain hydrophobically modified nano-alumina; wherein the mass ratio of oleic acid, N,N-dimethylformamide, N,N'-dicyclohexylcarbodiimide, N-hydroxysuccinimide and surface-modified nano-alumina is (5-8):(95-190):(3.7-7.4):(2.1-4.2):(3-8);
[0037] In the above process, the carboxyl groups in the oleic acid undergo amidation reaction with part of the amino groups on the surface of the surface-modified nano-alumina to obtain hydrophobic-modified nano-alumina containing long hydrophobic chains.
[0038] Step S2, adding hydrophobically modified nano-alumina to deionized water, ultrasonically treating for 10-20 minutes, then adding a modified binder, stirring and reacting for 10-20 minutes, and then ultrasonically treating for 10-20 minutes to obtain a wear-resistant and anti-corrosion coating; wherein the mass ratio of hydrophobically modified nano-alumina, deionized water, and modified binder is (0.6-1.2):(6-10):(20-30);
[0039] In the above process, a large number of hydroxyl groups in the chitosan network structure on the surface of the hydrophobically modified nano-alumina dehydrate and condense with the hydroxyl groups in the aluminum phosphate and polytannic acid in the modified binder to form an organic-inorganic three-dimensional cross-linked network.
[0040] The non-magnetic hard alloy composite material is prepared by the preparation method of the non-magnetic hard alloy composite material.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The present invention starts from optimizing the components of cemented carbide and coating with wear-resistant and anti-corrosion coating, combining the inside and outside to obtain a non-magnetic cemented carbide composite material with excellent wear resistance, corrosion resistance and toughness. Specifically:
[0043] 1. First, in the preparation process of non-magnetic cemented carbide, the present invention deposits and coats nano nickel on the surface of tungsten carbide by a solution method. Compared with the method of directly adding nickel in the traditional process, the problem of poor wettability of nickel on the surface of tungsten carbide can be improved, so that the nickel of the bonding phase is evenly distributed on the surface of tungsten carbide, the sintering property of nickel-coated tungsten carbide is improved, the density of the alloy is improved, and the hardness and corrosion resistance of the alloy are improved while maintaining the toughness of the alloy;
[0044] Secondly, the addition of metal yttrium powder can enrich harmful impurities such as S and Ca in the alloy, change the existence form of these harmful impurities, purify the interface, purify impurities, reduce the porosity of the alloy, and improve the density; tungsten carbide replaces the metal chromium in the traditional process. On the one hand, it can increase the carbon content in the raw materials, prevent the decarburization of the cemented carbide by the oxygen element in the rare earth oxide, and prevent the product cracking during the sintering process. The problem ensures the structural stability of the alloy, thereby ensuring the original bending strength and corrosion resistance of the non-magnetic cemented carbide. On the other hand, it also prevents the generation of a large amount of nickel-chromium alloy in the non-magnetic cemented carbide to destroy the original structure of the non-magnetic cemented carbide, resulting in a decrease in the performance of the non-magnetic cemented carbide.
[0045] In addition, ball milling combined with surfactant-assisted hydrothermal method was used to prepare lanthanum oxide-doped ultrafine composite powder. The addition of surfactant enabled lanthanum oxide and chromium carbide to be more evenly distributed in the alloy, improving the effectiveness of lanthanum oxide and chromium carbide. The addition of lanthanum oxide had a significant inhibitory effect on the growth of tungsten carbide grains, and grain refinement helped to improve the hardness and toughness of the alloy. The addition of lanthanum oxide reduced the porosity of the alloy and improved the corrosion resistance of the alloy.
[0046] In addition, silicon carbide whiskers play a role in grain refinement, crack deflection, crack bridging and microcrack toughening, thereby improving the hardness and toughness of the alloy. Moreover, during the sintering process, silicon carbide decomposes and reacts with nickel to generate free carbon. The generation of free carbon can promote grain growth, and work together with silicon carbide whiskers and chromium carbide to prevent the grains from being too small and reasonably adjust the grain size. In addition, free carbon can also eliminate the influence of oxygen in lanthanum oxide on the entire preparation process.
[0047] 2. The present invention connects modified black phosphorus nanosheets, hydrophobically modified nano-alumina and aluminum phosphate binder through covalent bonds to form an organic-inorganic three-dimensional cross-linked network: the lamellar structure of the black phosphorus nanosheets is combined with the spherical structure of the nano-alumina, the lamellar structure blocks the straight-through holes in the coating and can play a lubricating role, the spherical nano-alumina not only has high hardness but can further fill the micropores between the coating and the alloy substrate, the combination of two nanomaterials with different structures improves the wear resistance and corrosion resistance of the coating; the rich hydroxyl and phosphorus groups in the organic-inorganic three-dimensional cross-linked network structure enable the coating to directly form a strong binding force with the alloy substrate, thereby improving the adhesion of the coating;
[0048] Furthermore, the present invention performs a double passivation treatment on the black phosphorus nanosheets by using polytannic acid and cerium. The polytannic acid can neutralize the free radicals on the surface of the black phosphorus nanosheets and complex with cerium to form a polymer film to isolate oxygen and water, thereby solving the problem of poor stability of the black phosphorus nanosheets and extending the service life of the black phosphorus nanosheets. Although the addition of tannic acid and cerium will have a certain negative impact on the lubrication effect of the black phosphorus nanosheets, the polytannic acid grafting can improve the dispersibility of the black phosphorus nanosheets in the wear-resistant and anti-corrosion coating and the bonding strength with the aluminum phosphate binder, so that the black phosphorus nanosheets show long-lasting and efficient corrosion resistance and wear resistance. In addition, polytannic acid and cerium are both excellent corrosion inhibitors, which can delay or prevent metal corrosion and achieve active corrosion protection. Combined with the passive corrosion protection of the physical barrier of the nano black phosphorus sheets, better corrosion protection effect can be achieved.
[0049] In addition, the nano-alumina is surface-modified and hydrophobicized. On the one hand, more reactive hydroxyl groups are introduced to combine with the modified binder to improve the dispersibility of the nano-alumina. On the other hand, long hydrophobic chains are introduced on the surface of the nano-alumina to improve the hydrophobicity, thereby improving the corrosion resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 It is a process flow chart of the preparation method of the non-magnetic hard alloy composite material of the present invention;
[0051] Figure 2 It is a comparison chart of hardness test of non-magnetic cemented carbide of Examples 2-4 and Examples 11-13 of the present invention;
[0052] Figure 3 is a comparison diagram of wear volume tests of the non-magnetic cemented carbide composite materials of Examples 2-4 and 11-13 of the present invention;
[0053] Figure 4 It is a comparison chart of corrosion potential tests of the non-magnetic cemented carbide composite materials of Examples 2-4 and Examples 11-13 of the present invention. DETAILED DESCRIPTION
[0054] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example 1
[0055] This embodiment discloses a method for preparing a wear-resistant and anti-corrosion coating, comprising the following steps:
[0056] Step S1, preparing a modified binder and hydrophobically modified nano-alumina;
[0057] Wherein, preparing the modified binder comprises the following steps:
[0058] In a dark environment and nitrogen atmosphere, the black phosphorus nanosheet dispersion was ultrasonically treated for 100 minutes, tannic acid was added, and the reaction was stirred at a speed of 200 r / min for 5 hours, and then cerium nitrate was added, and the reaction was continued for 4 hours, centrifuged, and washed to obtain modified black phosphorus nanosheets, wherein the mass ratio of black phosphorus nanosheets, tannic acid, and cerium nitrate in the black phosphorus nanosheet dispersion was 1:1.1:0.2;
[0059] Aluminum hydroxide and 55 wt % phosphoric acid aqueous solution were mixed in a mass ratio of 23.4:18, and stirred at 95° C. for 180 min to obtain an aluminum phosphate binder; the aluminum phosphate binder was added to deionized water, ultrasonically treated for 15 min, and then modified black phosphorus nanosheets were added, the mass ratio of the aluminum phosphate binder, deionized water, and modified black phosphorus nanosheets was 6:15:0.6, and stirred for 15 min to obtain a modified binder;
[0060] The preparation of hydrophobically modified nano-alumina comprises the following steps:
[0061] Disperse chitosan in N,N-dimethylformamide under stirring conditions, add 3-(2,3-epoxypropoxy)propyltrimethoxysilane, stir and react at 80°C for 24 hours, then add nano-alumina, keep the temperature unchanged and continue to stir and react for 24 hours, centrifuge, wash the centrifugal product with ethanol, deionized water and acetone in turn, and dry at room temperature for 25 hours to obtain surface-modified nano-alumina;
[0062] Among them, the mass ratio of chitosan, N,N-dimethylformamide, 3-(2,3-epoxypropyloxy)propyltrimethoxysilane, and nano-alumina is 3.5:285:0.8:3;
[0063] Dissolve oleic acid in N,N-dimethylformamide, add N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide, stir at a speed of 250r / min for 3h, then add surface-modified nano-alumina under stirring, adjust the pH of the reaction mixture to 5.5 with a 1mol / L hydrochloric acid aqueous solution, react in a nitrogen atmosphere for 24h, filter after the reaction, wash the filter cake with methanol and dry it at 65°C for 15h to obtain hydrophobically modified nano-alumina;
[0064] Among them, the mass ratio of oleic acid, N,N-dimethylformamide, N,N'-dicyclohexylcarbodiimide, N-hydroxysuccinimide, and surface-modified nano-alumina is 6.5:142:5.6:3.2:5.5;
[0065] Step S2, adding the hydrophobically modified nano-alumina into deionized water, ultrasonically treating for 15 minutes, then adding the modified binder, stirring and reacting for 15 minutes, and then ultrasonically treating for 15 minutes to obtain a wear-resistant and anti-corrosion coating;
[0066] Among them, the mass ratio of hydrophobically modified nano-alumina, deionized water and modified binder is 0.8:8:25. Example 2
[0067] This embodiment discloses a method for preparing a non-magnetic cemented carbide composite material, comprising the following steps:
[0068] Step (1) nickel nitrate hexahydrate, nickel acetate tetrahydrate and triethanolamine are mixed in a molar ratio of 8:1:4.5 to obtain a nickel precursor solution; the nickel precursor solution is added to tungsten carbide powder, evaporated, and heated to 480° C. at a heating rate of 5° C. / min in an argon atmosphere to obtain nickel-coated tungsten carbide, wherein the nickel content in the nickel-coated tungsten carbide is 12wt%;
[0069] Step (2) mixing nickel-coated tungsten carbide, yttrium powder and chromium carbide powder in a mass ratio of 82.4:0.1:0.6, adding ethanol, ball milling, drying at 70° C. for 3 h, grinding, and passing through a 180-mesh sieve to obtain a composite powder; wherein the ball milling conditions are: ball-to-material ratio of 2:1, solid-liquid ratio of 1:3, ball milling speed of 34 r / min, and ball milling time of 36 h;
[0070] Step (3) adding hexadecyltrimethylammonium bromide and the composite powder into deionized water, stirring at a speed of 120 r / min for 20 min at room temperature, then adding lanthanum chloride hexahydrate, continuing stirring for 60 min, then dropping 25 wt % ammonia water at a speed of 0.5 mL / min, stirring at a speed of 400 r / min for 40 min, transferring to a closed container, reacting at 170° C. for 28 h, cooling to room temperature, filtering, washing, and vacuum drying at 70° C. for 15 h to obtain a lanthanum oxide-doped ultrafine composite powder with a particle size of 100-300 nm;
[0071] The mass ratio of hexadecyltrimethylammonium bromide, composite powder, deionized water, lanthanum chloride hexahydrate, and 25wt% ammonia water is 7.3:8.9:200:0.03:4.5;
[0072] Step (4) mixing lanthanum oxide doped ultrafine composite powder, molybdenum powder and silicon carbide whisker in a mass ratio of 82:0.7:0.9, adding ethanol, ball milling, drying at 70° C. for 3 h, grinding, and passing through an 80-mesh sieve to obtain a premix, wherein the ball milling conditions are as follows: ball milling speed of 200 r / min, ball milling time of 150 min, ball-to-material ratio of 6:1, and solid-liquid ratio of 1:3;
[0073] Step (5) forming the premix by dry pressing to form a rough blank, and then performing cold isostatic pressing to form a green body, and finally performing microwave sintering to obtain a non-magnetic cemented carbide, wherein the cold isostatic pressing method: increasing the pressure to 200 MPa within 3 minutes and maintaining the pressure for 5 minutes; the microwave sintering method: in an argon atmosphere, increasing the temperature from room temperature to 900°C at a heating rate of 3°C / min and maintaining the temperature for 15 minutes, then increasing the temperature to 1450°C at a heating rate of 15°C / min and maintaining the temperature for 15 minutes, and naturally cooling to room temperature;
[0074] Step (6) spraying the wear-resistant and anti-corrosion coating onto the surface of the non-magnetic cemented carbide with a coating thickness of 100 μm, and heat-treating the surface at 110° C. and 210° C. for 70 min each, respectively, to obtain a non-magnetic cemented carbide composite material. Example 3
[0075] This embodiment discloses a method for preparing a non-magnetic cemented carbide composite material, comprising the following steps:
[0076] Step (1) nickel nitrate hexahydrate, nickel acetate tetrahydrate and triethanolamine are mixed in a molar ratio of 10:1:5.5 to obtain a nickel precursor solution; the nickel precursor solution is added to tungsten carbide powder, evaporated, and heated to 520° C. at a heating rate of 10° C. / min in an argon atmosphere to obtain nickel-coated tungsten carbide, wherein the nickel content in the nickel-coated tungsten carbide is 16wt%;
[0077] Step (2) mixing nickel-coated tungsten carbide, yttrium powder and chromium carbide powder in a mass ratio of 83.6:1.2:0.8, adding ethanol, ball milling, drying at 90° C. for 3 h, grinding, and passing through a 200-mesh sieve to obtain a composite powder; wherein the ball milling conditions are: ball-to-material ratio of 4:1, solid-liquid ratio of 1:6, ball milling speed of 36 r / min, and ball milling time of 64 h;
[0078] Step (3) adding hexadecyltrimethylammonium bromide and the composite powder into deionized water, stirring at a speed of 160 r / min for 20 min at room temperature, then adding lanthanum chloride hexahydrate, continuing stirring for 90 min, then dripping 25 wt % ammonia water at a speed of 1 mL / min, stirring at a speed of 500 r / min for 20 min, transferring to a closed container, reacting at 180° C. for 20 h, cooling to room temperature, filtering, washing, and vacuum drying at 90° C. for 10 h to obtain lanthanum oxide doped ultrafine composite powder with a particle size of 100-300 nm;
[0079] The mass ratio of hexadecyltrimethylammonium bromide, composite powder, deionized water, lanthanum chloride hexahydrate, and 25wt% ammonia water is 14.6:18:500:0.1:9;
[0080] Step (4) mixing lanthanum oxide doped ultrafine composite powder, molybdenum powder and silicon carbide whisker in a mass ratio of 83.5:0.7:2, adding ethanol, ball milling, drying at 90° C. for 2 h, grinding, and passing through a 100-mesh sieve to obtain a premix, wherein the ball milling conditions are: ball milling speed of 300 r / min, ball milling time of 100 min, ball-to-material ratio of 8:1, and solid-liquid ratio of 1:6;
[0081] Step (5) forming the premix by dry pressing to form a rough blank, and then performing cold isostatic pressing to form a blank, and finally performing microwave sintering to obtain a non-magnetic cemented carbide, wherein the cold isostatic pressing method: increasing the pressure to 300 MPa within 5 minutes and maintaining the pressure for 3 minutes; the microwave sintering method: in an argon atmosphere, increasing the temperature from room temperature to 1000°C at a heating rate of 5°C / min and maintaining the temperature for 10 minutes, then increasing the temperature to 1500°C at a heating rate of 20°C / min and maintaining the temperature for 15 minutes, and naturally cooling to room temperature;
[0082] Step (6) spraying the wear-resistant and anti-corrosion coating onto the surface of the non-magnetic cemented carbide with a coating thickness of 120 μm, and heat treating at 120° C. and 220° C. for 50 min each, respectively, to obtain a non-magnetic cemented carbide composite material. Example 4
[0083] This embodiment discloses a method for preparing a non-magnetic cemented carbide composite material, comprising the following steps:
[0084] Step (1) nickel nitrate hexahydrate, nickel acetate tetrahydrate and triethanolamine are mixed in a molar ratio of 9:1:5 to obtain a nickel precursor solution; the nickel precursor solution is added to tungsten carbide powder, evaporated, and heated to 500° C. at a heating rate of 8° C. / min in an argon atmosphere to obtain nickel-coated tungsten carbide, wherein the nickel content in the nickel-coated tungsten carbide is 14wt%;
[0085] Step (2) mixing nickel-coated tungsten carbide, yttrium powder and chromium carbide powder in a mass ratio of 83:0.6:0.7, adding ethanol, ball milling, drying at 80° C. for 2.5 h, grinding, and passing through a 200-mesh sieve to obtain a composite powder; wherein the ball milling conditions are: ball-to-material ratio of 3:1, solid-liquid ratio of 1:5, ball milling speed of 35 r / min, and ball milling time of 50 h;
[0086] Step (3) adding hexadecyltrimethylammonium bromide and the composite powder into deionized water, stirring at a speed of 140 r / min for 30 min at room temperature, then adding lanthanum chloride hexahydrate, continuing stirring for 80 min, then dropping 25 wt % ammonia water at a speed of 0.8 mL / min, stirring at a speed of 450 r / min for 30 min, transferring to a closed container, reacting at 175° C. for 24 h, cooling to room temperature, filtering, washing, and vacuum drying at 80° C. for 12 h to obtain lanthanum oxide doped ultrafine composite powder with a particle size of 100-300 nm;
[0087] The mass ratio of hexadecyltrimethylammonium bromide, composite powder, deionized water, lanthanum chloride hexahydrate, and 25wt% ammonia water is 11:13.5:350:0.06:6.8;
[0088] Step (4) mixing lanthanum oxide doped ultrafine composite powder, molybdenum powder and silicon carbide whisker in a mass ratio of 82.7:0.7:1.5, adding ethanol, ball milling, drying at 80° C. for 2.5 h, grinding, and passing through a 100-mesh sieve to obtain a premix, wherein the ball milling conditions are: ball milling speed of 250 r / min, ball milling time of 120 min, ball-to-material ratio of 7:1, and solid-liquid ratio of 1:5;
[0089] Step (5) forming the premix by dry pressing to form a rough blank, and then performing cold isostatic pressing to form a blank, and finally performing microwave sintering to obtain a non-magnetic cemented carbide, wherein the cold isostatic pressing method: increasing the pressure to 250 MPa within 4 minutes and maintaining the pressure for 4 minutes; the microwave sintering method: in an argon atmosphere, increasing the temperature from room temperature to 950°C at a heating rate of 4°C / min and maintaining the temperature for 15 minutes, then increasing the temperature to 1480°C at a heating rate of 18°C / min and maintaining the temperature for 12 minutes, and naturally cooling to room temperature;
[0090] Step (6) spraying the wear-resistant and anti-corrosion coating onto the surface of the non-magnetic cemented carbide with a coating thickness of 110 μm, and heat-treating at 115° C. and 215° C. for 60 min each, respectively, to obtain a non-magnetic cemented carbide composite material.
[0091] The wear-resistant and anti-corrosion coating used in the above-mentioned Examples 2-4 is the wear-resistant and anti-corrosion coating prepared in Example 1.
[0092] Comparative Example 1
[0093] Comparative Example 1 Compared with Example 1, in the process of preparing the modified black phosphorus nanosheets in Comparative Example 1, tannic acid was not added, and other conditions remained unchanged.
[0094] Comparative Example 2
[0095] Comparative Example 2 Compared with Example 1, in the process of preparing the modified black phosphorus nanosheets in Comparative Example 2, no cerium nitrate was added, and other conditions remained unchanged.
[0096] Comparative Example 3
[0097] Compared with Example 1, in the process of preparing the wear-resistant and anti-corrosion coating in Comparative Example 3, nano alumina is used instead of hydrophobically modified nano alumina, and other conditions remain unchanged.
[0098] Comparative Example 4
[0099] Compared with Example 1, in Comparative Example 4, during the preparation of the wear-resistant and anti-corrosion coating, aluminum phosphate binder is used instead of modified binder, and other conditions remain unchanged.
[0100] Comparative Example 5
[0101] Compared with Example 1, in Example 5, no hydrophobic modified nano alumina was added during the preparation of the wear-resistant and anti-corrosion coating, that is, the modified binder in this comparative example is the final product - the wear-resistant and anti-corrosion coating, and other conditions remain unchanged.
[0102] Comparative Example 6
[0103] Comparative Example 6 Compared with Example 4, in the process of preparing the non-magnetic cemented carbide composite material, the wear-resistant and anti-corrosion coating in Comparative Example 1 was used in Comparative Example 6, and other conditions remained unchanged.
[0104] Comparative Example 7
[0105] Comparative Example 7 Compared with Example 4, in the process of preparing the non-magnetic cemented carbide composite material, the wear-resistant and anti-corrosion coating in Comparative Example 2 was used in Comparative Example 7, and other conditions remained unchanged.
[0106] Comparative Example 8
[0107] Comparative Example 8 Compared with Example 4, in the process of preparing the non-magnetic cemented carbide composite material, the wear-resistant and anti-corrosion coating in Comparative Example 3 was used in Comparative Example 8, and other conditions remained unchanged.
[0108] Comparative Example 9
[0109] Comparative Example 9 Compared with Example 4, in the process of preparing the non-magnetic cemented carbide composite material, the wear-resistant and anti-corrosion coating in Comparative Example 4 was used in Comparative Example 9, and other conditions remained unchanged.
[0110] Comparative Example 10
[0111] Comparative Example 10 Compared with Example 4, in the process of preparing the non-magnetic cemented carbide composite material, Comparative Example 10 adopts the wear-resistant and anti-corrosion coating in Comparative Example 5, and other conditions remain unchanged.
[0112] Comparative Example 11
[0113] Compared with Example 4, in Example 11, during the preparation of the composite powder, equal proportions of nickel powder and tungsten carbide are used instead of nickel-coated tungsten carbide, that is, the tungsten carbide is not nickel-coated in this comparative example, and the nickel powder is directly added to the composite powder, while other conditions remain unchanged.
[0114] Comparative Example 12
[0115] Compared with Example 4, in the process of preparing lanthanum oxide doped ultrafine composite powder, Comparative Example 12 adopts the same method as that of preparing composite powder to directly add lanthanum oxide into the composite powder to obtain lanthanum oxide doped composite powder, while other conditions remain unchanged.
[0116] Comparative Example 13
[0117] Comparative Example 13 Compared with Example 4, in the process of preparing the premix in Comparative Example 13, no silicon carbide whiskers were added, and other conditions remained unchanged.
[0118] In the above embodiments and comparative examples: silicon carbide whiskers, with a diameter of 0.1-1 μm and a length of 5-30 μm, with the brand name D500B, are from Guangzhou Hongwu Materials Technology Co., Ltd.; black phosphorus nanosheet dispersion, with the product number BKMK506-01, is obtained by dispersing black phosphorus nanosheets in deionized water, with a concentration of 0.2 mg / mL, a nanosheet thickness of 1-10 layers, and a size of 0.1-5 μm, and is from Suzhou Beike Nanotechnology Co., Ltd.; nano-alumina, with an average particle size of 100 nm, with the product number YM-Al2O3-N100, is from Yumu (Ningbo) New Materials Co., Ltd.; chitosan, with a molecular weight of 190,000-310,000 Da, a viscosity of 200-800 cPs, and a deacetylation degree of 75%-85%, is from Sigma-Aldrich.
[0119] Experimental example
[0120] Hardness test: The non-magnetic cemented carbide samples (not coated with wear-resistant and anti-corrosion coating) prepared in Examples 2-4 and Comparative Examples 11-13 were taken, and the Vickers hardness was measured on the surface of the sintered samples using a digital microhardness tester (HVS-1000, Shenzhen Zhongzheng Instrument Co., Ltd., Shenzhen, China) with a load of 196N and a holding time of 10s. The test results are shown in Table 1:
[0121]
[0122] It can be seen from the test results of Table 1 that the non-magnetic cemented carbides prepared in Examples 2-4 of the present invention have excellent hardness. It can be seen from the comparison between Comparative Example 11 and Example 4 that, compared with directly adding nickel in the traditional way, coating tungsten carbide with nano-nickel can effectively improve the problem of poor wettability between nickel and tungsten carbide, thereby improving the hardness of the alloy; it can be seen from the comparison between Comparative Example 12 and Example 4 that, compared with directly adding lanthanum oxide, the lanthanum oxide-doped ultrafine composite powder prepared by ball milling combined with surfactant-assisted hydrothermal method can make lanthanum oxide and chromium carbide more evenly distributed in the alloy, thereby improving the effectiveness of lanthanum oxide and chromium carbide, thereby improving the hardness of the alloy; it can be seen from the comparison between Comparative Example 13 and Example 4 that silicon carbide whiskers play the role of grain refinement, crack deflection, crack bridging and microcrack toughening, and, during the sintering process, the reaction finally generates free carbon, which reasonably adjusts the grain size, thereby having a positive effect on the hardness of the alloy.
[0123] 2. Wear volume test: Take the non-magnetic cemented carbide composite material samples prepared in Examples 2-4 and Comparative Examples 6-13, and test the wear volume of the surface of each group of samples. The pin-disc friction tester (MPX-3X, Jinan Hengxu Testing Machine Technology Co., Ltd.) is used for characterization. The experiment is carried out at room temperature and a relative humidity of 50±5%.
[0124] 3. Anti-corrosion performance test: The non-magnetic cemented carbide composite materials prepared in Examples 2-4 and Comparative Examples 6-13 were tested for anti-corrosion performance. The test method is as follows:
[0125] The corrosion behavior of each group of samples in 3.5% NaCl aqueous solution was studied using an electrochemical workstation (CHI 660E, Shanghai Chenhua Instrument Co., Ltd.). The corrosion experiment was carried out at room temperature, with Ag / AgCl electrode as the reference electrode and platinum foil electrode as the counter electrode. The corrosion potential (Ecorr) of the prepared samples was analyzed in the range of −1.0~0.4V with a scanning speed of 1mV / s.
[0126] The wear volume and corrosion potential test results are shown in Table 2:
[0127]
[0128] It can be seen from the test results in Table 2 that the non-magnetic cemented carbide composite materials prepared in Examples 2-4 of the present invention have excellent wear resistance and corrosion resistance. From the comparison of Comparative Examples 6, 7, and 9 with Example 4, it can be seen that adding modified black phosphorus nanosheets to the wear-resistant and anti-corrosion coating can significantly improve the wear resistance and corrosion resistance of the non-magnetic cemented carbide composite material. On the one hand, it is due to the physical barrier and lubricity of the sheet structure of the black phosphorus nanosheets themselves. On the other hand, the access of polytannic acid and the loading of cerium show the effects of improving the stability, dispersibility, and bonding strength of the black phosphorus nanosheets with the coating, thereby making the non-magnetic cemented carbide composite material have excellent performance; From the comparison of Comparative Examples 8 and 10 with Example 4, it can be seen that the hydrophobic modified nano-alumina also has a very important influence on the wear resistance and corrosion resistance of the non-magnetic cemented carbide composite material. On the one hand, it is due to the hardness of the rigid inorganic nano-alumina particles themselves. On the other hand, the nano-alumina particles fill the pores of the coating. Furthermore, by surface modification of the nano-alumina, a large number of functional groups can be introduced to form a cross-linked network with the coating matrix, and oleic acid grafted reaction functional groups are provided. Amino groups are present in the reaction mixture, thereby improving the dispersibility and hydrophobicity of nano-alumina, and further improving the wear resistance and corrosion resistance of the material. By comparing comparative examples 11-13 with Example 4, it can be seen that the wear-resistant and anti-corrosion coating of the present invention has excellent wear resistance, so the optimization result of the internal composition of the alloy is not obviously reflected in the wear test. However, it can be seen from the test results in Table 1 that the present invention coats a coating with excellent wear resistance on the surface of the alloy, optimizes the internal composition of the cemented carbide, and combines the inside and the outside to make the non-magnetic cemented carbide composite material of the present invention have excellent hardness and wear resistance. Even if the surface coating is destroyed, the internal alloy can still exhibit good wear resistance by virtue of its own high hardness. By comparing comparative examples 11-12 with Example 4, it can be seen that the lanthanum oxide-doped ultrafine composite powder prepared by coating tungsten carbide with nano-nickel and ball milling combined with surfactant-assisted hydrothermal method can improve the density of the alloy, reduce the contact area between tungsten carbide and nickel in the alloy and the corrosive liquid, and thus improve the corrosion resistance of the material.
[0129] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a non-magnetic cemented carbide composite material, characterized in that: The following steps are involved: Step (1) treating tungsten carbide with a nickel precursor solution to obtain nickel-coated tungsten carbide; Step (2) mixing nickel-coated tungsten carbide, yttrium powder and chromium carbide powder, ball milling, drying, grinding and sieving to obtain a composite powder; Step (3) treating the composite powder with lanthanum chloride hexahydrate, and using ball milling combined with surfactant-assisted hydrothermal method to obtain lanthanum oxide-doped ultrafine composite powder; Step (4) mixing the lanthanum oxide doped ultrafine composite powder, molybdenum powder and silicon carbide whisker, ball milling, drying, grinding and sieving to obtain a premix; Step (5) forming the premix into a rough blank by dry pressing, then performing cold isostatic pressing to form a green body, and finally performing microwave sintering to obtain a non-magnetic hard alloy; Step (6) spraying the wear-resistant and anti-corrosion coating on the surface of the non-magnetic cemented carbide, heat treating, and curing to obtain a non-magnetic cemented carbide composite material; The method for preparing the wear-resistant and anti-corrosion coating comprises the following steps: Step S1, preparing a modified binder and hydrophobically modified nano-alumina; Wherein, preparing the modified binder comprises the following steps: Using black phosphorus nanosheets, tannic acid and cerium nitrate as raw materials, reacting to obtain modified black phosphorus nanosheets; Aluminum hydroxide reacts with phosphoric acid to obtain an aluminum phosphate binder, which then reacts with modified black phosphorus nanosheets to obtain a modified binder; The preparation of hydrophobically modified nano-alumina comprises the following steps: The nano-alumina is modified by chitosan and 3-(2,3-epoxypropoxy)propyltrimethoxysilane to obtain surface-modified nano-alumina; The surface-modified nano-alumina is treated with oleic acid to obtain hydrophobic-modified nano-alumina; Step S2: The hydrophobically modified nano-alumina reacts with the modified binder to obtain a wear-resistant and anti-corrosion coating.
2. The method for preparing the non-magnetic cemented carbide composite material according to claim 1, characterized in that: In the step (1), the preparation method of nickel-coated tungsten carbide is as follows: a nickel precursor solution is added to tungsten carbide powder, evaporated, and heated to 480-520° C. at a heating rate of 5-10° C. / min in an argon atmosphere to obtain nickel-coated tungsten carbide, wherein the nickel content in the nickel-coated tungsten carbide is 12-16wt%; the nickel precursor solution is obtained by mixing nickel nitrate hexahydrate, nickel acetate tetrahydrate, and triethanolamine in a molar ratio of (8-10):1:(4.5-5.5).
3. The method for preparing the non-magnetic cemented carbide composite material according to claim 1, characterized in that: In the step (2), the mass ratio of nickel-coated tungsten carbide, yttrium powder and chromium carbide powder is (82.4-83.6):(0.1-1.2):(0.6-0.8); drying conditions: drying at 70-90°C for 2-3h; sieving mesh size is 180-200 mesh; ball milling conditions: ball-to-material ratio is (2-4):1, solid-liquid ratio is 1:(3-6), ball milling speed is 34-36r / min, and ball milling time is 36-64h.
4. The method for preparing the non-magnetic cemented carbide composite material according to claim 1, characterized in that: In the step (3), the preparation method of lanthanum oxide doped ultrafine composite powder is as follows: cetyltrimethylammonium bromide and composite powder are added to deionized water, stirred at a speed of 120-160r / min for 20-40min at room temperature, lanthanum chloride hexahydrate is added, stirring is continued for 60-90min, ammonia water is added dropwise at a speed of 0.5-1mL / min, stirred at a speed of 400-500r / min for 20-40min, transferred to a closed container, reacted at 170-180°C for 20-28h, cooled to room temperature, filtered, washed, and dried to obtain lanthanum oxide doped ultrafine composite powder with a particle size of 100-300nm; wherein the mass ratio of cetyltrimethylammonium bromide, composite powder, deionized water, lanthanum chloride hexahydrate, and ammonia water is (7.3-14.6):(8.9-18):(200-500):(0.03-0.1):(4.5-9).
5. The method for preparing the non-magnetic cemented carbide composite material according to claim 1, characterized in that: In the step (4), the mass ratio of lanthanum oxide doped ultrafine composite powder, molybdenum powder and silicon carbide whisker is (82-83.5):0.7:(0.9-2); drying conditions: drying at 70-90°C for 2-3h; sieving mesh size is 80-120 mesh; ball milling conditions: ball milling speed is 200-300r / min, ball milling time is 100-150min, ball to material ratio is (6-8):1, and solid-liquid ratio is 1:(3-6).
6. The method for preparing the non-magnetic cemented carbide composite material according to claim 1, characterized in that: In the step (5), the cold isostatic pressing method is: the pressure is increased to 200-300 MPa within 3-5 minutes, and the pressure is maintained for 3-5 minutes.
7. The method for preparing the non-magnetic cemented carbide composite material according to claim 1, characterized in that: In the step (5), the microwave sintering method is: in an argon atmosphere, the temperature is increased from room temperature to 900-1000°C at a heating rate of 3-5°C / min and kept at this temperature for 10-20 minutes, then the temperature is increased to 1450-1500°C at a heating rate of 15-20°C / min and kept at this temperature for 10-15 minutes, and then naturally cooled to room temperature.
8. The method for preparing the non-magnetic cemented carbide composite material according to claim 1, characterized in that: In the step (6), the spray thickness of the wear-resistant and anti-corrosion coating is 100-120 μm; the heat treatment method is: heat treatment at 110-120° C. and 210-220° C. for 50-70 minutes each.
9. The method for preparing the non-magnetic cemented carbide composite material according to claim 1, characterized in that: In step (6), the method for preparing the wear-resistant and anti-corrosion coating specifically comprises the following steps: Step S1, preparing a modified binder and hydrophobically modified nano-alumina; Wherein, preparing the modified binder comprises the following steps: In a dark environment and nitrogen atmosphere, the black phosphorus nanosheet dispersion was ultrasonically treated for 80-120 min, tannic acid was added, and the reaction was stirred at a speed of 150-250 r / min for 4.5-5.5 h, and then cerium nitrate was added, and the reaction was continued for 3.5-4.5 h, centrifuged, and washed to obtain modified black phosphorus nanosheets, wherein the mass ratio of black phosphorus nanosheets, tannic acid, and cerium nitrate was 1:(1-1.2):(0.15-0.25); Aluminum hydroxide and 50-60wt% phosphoric acid aqueous solution are mixed in a mass ratio of 23.4:(16.3-19.6), and stirred at 90-100°C for 150-200min to obtain an aluminum phosphate binder; the aluminum phosphate binder is added to deionized water, ultrasonically treated for 10-20min, and then modified black phosphorus nanosheets are added and stirred for 10-20min to obtain a modified binder; wherein the mass ratio of the aluminum phosphate binder, deionized water, and modified black phosphorus nanosheets is (3.5-8.4):(10-20):(0.3-0.9); The preparation of hydrophobically modified nano-alumina comprises the following steps: Disperse chitosan in N,N-dimethylformamide under stirring conditions, add 3-(2,3-epoxypropoxy)propyltrimethoxysilane, stir and react at 75-85°C for 20-28h, then add nano-alumina, keep the temperature unchanged and continue to stir and react for 20-28h, centrifuge, wash, and dry to obtain surface-modified nano-alumina; wherein the mass ratio of chitosan, N,N-dimethylformamide, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, and nano-alumina is (2-5):(190-475):(0.5-1):(2.5-3.5); Dissolve oleic acid in N,N-dimethylformamide, then add N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide, stir at a speed of 200-300r / min for 2.5-3.5h, then add surface-modified nano-alumina under stirring, adjust the pH of the reaction mixture to 5.4-5.6 with 1mol / L hydrochloric acid aqueous solution, react in a nitrogen atmosphere for 20-28h, filter, wash and dry after the reaction to obtain hydrophobically modified nano-alumina; wherein the mass ratio of oleic acid, N,N-dimethylformamide, N,N'-dicyclohexylcarbodiimide, N-hydroxysuccinimide and surface-modified nano-alumina is (5-8):(95-190):(3.7-7.4):(2.1-4.2):(3-8); Step S2, adding hydrophobically modified nano-alumina to deionized water, ultrasonically treating for 10-20 minutes, then adding a modified binder, stirring and reacting for 10-20 minutes, and then ultrasonically treating for 10-20 minutes to obtain a wear-resistant and anti-corrosion coating; wherein the mass ratio of hydrophobically modified nano-alumina, deionized water, and modified binder is (0.6-1.2):(6-10):(20-30).
10. A non-magnetic cemented carbide composite material prepared by the method for preparing a non-magnetic cemented carbide composite material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Vanadium-containing non-magnesium hard alloy and preparation method thereof
CN101265544A
WCoB-TiC composite ceramic tool material and preparation method thereof
CN106544605A
Water-based wear-resistant coating and preparation method thereof
CN112409867A